KESALAHAN KONSEPTUAL DALAM AKUNTANSI: STUDI DESKRIPTIF PADA MAHASISWA - Hasnidar Hasnidar (Accounting Student Series on Emerging Trends, 2026)
Conceptual errors in accounting are not exclusive to introductory courses; they persist and take more complex forms in intermediate-level courses. This study aims to describe the types of conceptual errors most frequently observed among accounting students during the teaching of Intermediate Financial Accounting 1 and 2, and to explore the contributing factors underlying these errors based on direct classroom experience. Using a qualitative descriptive approach grounded in practitioner observation, data were gathered through systematic classroom observation, analysis of student assignments and examination scripts, and informal reflective discussions with students across multiple semesters. Two dominant themes of conceptual error were identified that (1) misunderstanding of the recoverable amount concept and impairment recognition under PSAK 48; and (2) confusion in distinguishing temporary and permanent differences in deferred tax accounting under PSAK 46. Contributing factors include weak retention of foundational concepts from prior accounting courses, difficulty abstracting multi-standard interactions, and over-reliance on procedural memorization. This study contributes to accounting education literature by offering classroom-grounded, observational insights into conceptual error patterns at the intermediate level, with practical implications for instructors of intermediate accounting courses.